2000
DOI: 10.1007/s001470050376
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Palmaz stent insertion in the treatment of renal artery stenosis in kidney transplantation

Abstract: The aim of this study was to verify the safety and long-term efficacy of Palmaz stent insertion in the treatment of transplant renal artery stenosis (TRAS) in kidney transplantation. Nine of our transplanted patients were submitted to Palmaz stent insertion because of recurrence of renal artery stenosis after previous percutaneous transluminal angioplasty or because of severe ostial stenosis. The post-stenting results were excellent in all patients, with a follow-up period ranging from 1 to 3 years. The mean b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…We believe that these factors are even more important for the pediatric population, and strongly support PTA as the first-line treatment when an experienced team is available Expandable metallic prostheses have been used for stenosis of coronary, peripheral and renal arteries. Palmaz et al [15] first reported their use in native kidneys and since 1995 several papers reporting their use in RAS have been published [15,16,17,18,19,20]. We have placed a metallic stent in two of our patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We believe that these factors are even more important for the pediatric population, and strongly support PTA as the first-line treatment when an experienced team is available Expandable metallic prostheses have been used for stenosis of coronary, peripheral and renal arteries. Palmaz et al [15] first reported their use in native kidneys and since 1995 several papers reporting their use in RAS have been published [15,16,17,18,19,20]. We have placed a metallic stent in two of our patients.…”
Section: Discussionmentioning
confidence: 82%
“…The use of expandable metallic prostheses (stents) was reported for coronary, peripheral, and native renal vascular stenosis [15]. Its use in transplant RAS is limited and most papers include only adult patients [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Stents may be useful, especially in those with recurrence [ 56 ]. If there is signifi cant aortoiliac atherosclerotic disease or no response to angioplasty, surgery may be necessary.…”
Section: Treatment Of Trasmentioning
confidence: 98%
“…Although stents are not usually required to treat stenoses within the transplant artery or at the anastomosis, they have been used successfully and are needed routinely to treat the pseudo-transplant renal artery stenosis due to iliac atherosclerotic occlusive disease proximal to the takeoff of the transplant artery. 37 Surgical revascularization is reserved for patients in whom angioplasty or stenting has been unsuccessful or complicated. Surgical renal revascularization is difficult and is associated with significant mortality in the transplantation setting.…”
Section: Treatmentmentioning
confidence: 99%